Incidental finding at methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA): how to proceed? - Manero-Azua, Africa; Pereda, Arrate; Llano-Rivas, Isabel; Garin, Intza; Perez de Nanclares, Guiomar (Frontiers in Genetics, 2023)
Introduction: Since the advent of new generation sequencing, professionals are aware of the possibility of obtaining findings unrelated to the pathology under study. However, this possibility is usually forgotten in the case of studies aimed at a single gene or region. We report a case of a 16month-old girl with clinical suspicion of Silver-Russell syndrome (SRS).Methods: Following the international SRS consensus, methylation alterations and copy number variations (CNVs) at 11p15 region and maternal uniparental disomy of chromosome 7 were analysed and discarded by MS-MLPA.Results: Unexpectedly, the 11p15 region MS-MLPA showed a decrease in the signal of a copy number reference probe. Deletions affecting a single probe are inconclusive. So, we faced the ethical dilemma of whether it was appropriate to confirm this alteration with independent techniques and to offer a diagnostic possibility that was in no way related to clinical suspicion. Fortunately, in this particular case, the informed consent had not been specific to a particular pathology but to any disorder associated with growth failure. Performed alternative studies allowed the final diagnosis of 22q deletion syndrome.We demonstrate the importance of informing patients about the possibility of obtaining incidental findings in genetic techniques (not only in next generation sequencing) during pre-test genetic counselling consultations. In addition, we highlight the relevance of including in the informed consent the option of knowing these unexpected incidental findings as in some cases, this will help to elucidate the definitive diagnosis and provide the correct follow-up and treatment.